ENT 530 Social Media Portfolio: Sunny’s Spaghetti / Nurul Adzrin Abdullah Sani - Abdullah Sani, Nurul Adzrin (2021)
Sunny’s Spaghetti is headquartered in my own house in Rantau, Negeri Sembilan. The company is owned by me, Nurul Adzrin binti Abdullah Sani and also a few key partners such as my mother, my siblings and my suppliers. Our company is a new so we need to gain more experience in business. We are still in the process of realizing what aspects that we should do to improve to fulfil our future needs. The management of Sunny’s Spaghetti consists of co-owners which is my mother, Puan Fadillah binti Haji Khalid and my siblings which are Nurul Ain, Nurul Aqmar and Noramin. All of them are taking care of management roles in the company. In addition, we have assembled a board of advisors to provide management expertise which are Puan Fadillah binti Haji Khalid (my mother) and Encik Abdullah Sani bin Hassan (my father). This is because my mother already has experienced in doing business.